The Advantages and Disadvantages of Integrated Care Implementation in Central and Eastern Europe - Perspective from 9 CEE Countries - Kurpas, Donata; Stefanicka-Wojtas, Dorota; Shpakou, Andrei; Halata, David; Mohos, András; Skarbaliene, Aelita; Dumitra, Gindrovel; Klimatckaia, Ludmila; Bendova, Jana; Tkachenko, Victoria (International journal of integrated care, 2021)
INTRODUCTION: Health and social care systems in Central and Eastern European (CEE) countries have undergone significant changes and are currently dealing with serious problems of system disintegration, coordination and a lack of control over the market environment. DESCRIPTION: The increased health needs related to the ageing society and epidemiological patterns in these countries also require funding needs to increase, rationing to be reformed, sectors to be integrated (the managed care approach), and an analytical information base to be developed if supervision of new technological approaches is to improve. The period of system transitions in CEE countries entailed significant changes in their health systems, including health care financing. DISCUSSION: Large deficits in the public financing of health systems were just one of the challenges arising from the economic downturn of the 1990s, which was coupled with inflation, increasing unemployment, low salaries, a large informal sector and tax evasion in a number of CEE countries. During the communist period, there was universal access to a wide range of health services, proving it difficult to retain this coverage. As a result, many states sought to ration publicly funded health services - for example, through patient cost-sharing or decreasing the scope of basic benefits. Yet, not all of these reform plans were implemented, and in fact, some were rolled back or not implemented at all due to a lack of social or political consensus. CONCLUSION: CEE health systems had come to practice implicit rationing in the form of under-the-table payments from patients, quasi-formal payments to providers to compensate for lack of funding, and long waiting lists forcing patients to the private sector. All these difficulties pose a challenge to the implementation of integrated care.
Keywords: social care; Central and Eastern Europe; implementation; health care; integrated care